Students' perceptions toward the influence of teachers’ attitudes on English learning achievement - Fadhilah, Aisyah Nur; Warni, Silih (Universitas Muhammadiyah Malang, 2024)
This study investigates students' perceptions of the influence of teachers' attitudes on their English learning achievement in senior high schools. Employing a qualitative research design, data were gathered through observations and semi-structured interviews with nine students from a senior high school in Jakarta. The analysis revealed four key themes: Teachers’ Attitudes and Student Confidence, Adaptability in Teaching, Creating Positive Learning Environments, and Impact on Learning Achievement. The findings showed that positive teacher attitudes significantly boost student confidence, while negative attitudes diminish enthusiasm for learning. Adaptability in teaching methods, including the integration of technology and varied learning resources, was found to enhance student engagement. Additionally, creating positive and supportive learning environments through engaging teaching strategies, such as games and discussions, fostered student interest and motivation. Constructive feedback and practical language skills development were linked to improved academic performance and language proficiency. The study underscores the critical role of positive teacher attitudes and student-centered approaches in facilitating successful English language acquisition, highlighting the importance of fostering supportive and engaging learning environments to enhance students' academic achievements and language proficiency.